2016
DOI: 10.14336/ad.2015.1007
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Alzheimer’s Disease and the Rationale for Bioenergetics Based Therapies

Abstract: Alzheimer’s disease (AD) is a debilitating neurodegenerative disorder characterized by the progressive loss of cholinergic neurons, leading to the onset of severe behavioral, motor and cognitive impairments. It is a pressing public health problem with no effective treatment. Existing therapies only provide symptomatic relief without being able to prevent, stop or reverse the pathologic process. While the molecular basis underlying this multifactorial neurodegenerative disorder remains a significant challenge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
161
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(162 citation statements)
references
References 205 publications
(207 reference statements)
0
161
0
1
Order By: Relevance
“…Decreased ΔΨm, due to the uncoupling of electron flow from ATP synthesis by increased proton permeability of the inner mitochondrial membrane, can reduce ROS production at complex I by decreasing NAD(P)H/NAD(P) + and possibly by decreasing the life span of the semiquinone radical [39]. Such decrease in the mitochondrial membrane potential (ΔΨm) primarily attenuates mitochondrial RO production with a consequential decrease in mitochondrial Ca 2+ uptake [40], preventing mitochondrial calcium overload and the a b c d e f Fig. 5 Respective effect of Parkia biglobosa leaf extract (PBE) and catechin on basal ROS production (a and b), Ca 2+ − induced (c and d) and SNP-induced (e and f) aggravation of ROS generation in isolated rats' liver mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased ΔΨm, due to the uncoupling of electron flow from ATP synthesis by increased proton permeability of the inner mitochondrial membrane, can reduce ROS production at complex I by decreasing NAD(P)H/NAD(P) + and possibly by decreasing the life span of the semiquinone radical [39]. Such decrease in the mitochondrial membrane potential (ΔΨm) primarily attenuates mitochondrial RO production with a consequential decrease in mitochondrial Ca 2+ uptake [40], preventing mitochondrial calcium overload and the a b c d e f Fig. 5 Respective effect of Parkia biglobosa leaf extract (PBE) and catechin on basal ROS production (a and b), Ca 2+ − induced (c and d) and SNP-induced (e and f) aggravation of ROS generation in isolated rats' liver mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…This might account for the superior mitochondrial ROS mitigating property of PBE over catechin. Such mild depolarization has been attributed to the neuroprotective effect of a plant extract [42] and the protection of cardiomyocytes from oxidative stress [40]. In the case of PBE, further studies are warranted to identify the active molecules and the underlying mechanisms involved in its mild mitochondrial potential depolarization propensity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified structural and functional mitochondrial abnormalities in hippocampal neurones of AD patients compared with age-and sex-matched controls [213][214][215][216]. Such abnormalities include a significant reduction in mitochondrial numbers and exaggerated levels of oxidised mitochondrial DNA (mtDNA) and nitrated proteins in the cytoplasm in a pattern suggestive of impaired mitophagy or fission dynamics [215][216][217]. These mitochondrial abnormalities are accompanied by oxidative damage marked by 8-hydroxyguanosine and nitrotyrosine, indicating that the mitochondria are damaged by ROS and RNS during disease progression [213,218,219].…”
Section: Oxidative Stress and The Development Of Mitochondrial Dysfunmentioning
confidence: 99%
“…This leads to a continuous "vicious cycle" where dysfunctional mitochondria contribute to further ROS production, which can lead to further ROS-mediated oxidative damage to mitochondria [8]. Mitochondrial dysfunction is heavily implicated in the ageing process and the pathogenesis of age-related diseases such as Alzheimer's disease (AD) [16]. In AD it is believed that the accumulation of amyloid beta peptide interacts with mitochondria, leading to mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%